Closed-loop dynamic computations for adaptive behavior (articles based on SAB2018 conference). (June 2020) - Manoonpong, Poramate; Xiong, Xiaofeng; Larsen, Jørgen Christian
The Special Issue contains the selected articles presented at the 15th International Conference on the Simulation of Adaptive Behavior (SAB 2018). The conference took place during August 2018 in Frankfurt, Germany. The articles introduce different aspects of closed-loop dynamic computations for adaptive behavior in artificial agents. The aspects cover a range of adaptive behavior research from morphological computation to brain-body-environment interactions, nature-inspired special perception, and closed-loop online learning. SAB is a biennial conference; its next incarnation will be during September 2020, in Paris. If the papers in this issue inspire you, please consider submitting your work to the 2020 conference—who knows, next time it may be your paper in the Special Issue.